Gender and Economic Roles of Women in Fishing Communities after Coastal Infrastructure Development - Nisa, Fahrun; Abdul Kadir, Hatib (Social Sciences and Humanities Reviews, 2025)
Background:The development of coastal infrastructure such as breakwaters is often considered a technical solution to overcome the problem of sea waves, but its impact on the social dynamics of coastal communities, especially the division of labor and economic roles in fishing households, has rarely been studied in depth. Aims:This study aims to reveal how livelihood diversification becomes an adaptation strategy for the Njar Kulon fishing community, Kranji Village, in responding to changes in infrastructure, and how these changes affect gender roles in the family. Methods:This study uses a qualitative approach with ethnographic methods. Data were obtained through participant observation, in-depth interviews, and documentation of two fishing families as the main informants, as well as several supporting informants. The analysis was conducted using a domain and taxonomy approach based on the concept of material diagnostics and gender as performance. Result:The results of the study show that the construction of the brook limits women's access to the sea and encourages them to move to informal jobs on land. This change shifts women's economic role to be more dominant in the household, especially during the lean season. Diversifying livelihoods becomes a survival strategy taken by all family members. Conclusion:Physical infrastructure has complex social impacts, including the restructuring of gender roles in fishing families. Therefore, development planning in coastal areas needs to consider social aspects and involve community participation, especially women, so that development is responsive and sustainable.